Sinyal di Balik Angka: Menguak Rahasia Aset Pajak Tangguhan dalam Mendeteksi Praktik Manajemen Laba - Rifael Timasa Sinulingga; Rina Tjandra Kirana DP (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
Financial statements frequently serve as a strategic "battleground" between the management's interest in satisfying investors through high reported earnings and the necessity of minimizing corporate tax burdens. Amidst these conflicting interests, earnings management practices are often employed by management. This study aims to investigate the role of deferred tax assets (DTA) as a signal or indicator for detecting earnings management practices, particularly within the manufacturing sector. Unlike common discretionary accruals, the deferred tax component is often overlooked by investors and analysts due to the inherent complexity of accounting and tax standards. Utilizing a quantitative approach with Systematic Literature Review (SLR) model, this research expects to demonstrate that unusual fluctuations in deferred tax assets have a significant positive correlation with the probability of earnings manipulation. The findings of this study are projected to provide practical contributions for auditors, tax authorities, and investors in utilizing deferred tax components as an "early warning system" to assess the quality of a company's reported earnings.